A survey to understand farmers' perceptions and risk factors for hoof diseases including footrot in sheep in New South Wales, Australia - Smith, Karen; Whittington, Richard J.; Green, Alexandra C.; Dhand, Navneet K.; Moses, Alicia; Grove, Annie; Thane, Tegan; Dhungyel, Om P. (Frontiers in Veterinary Science, 2022)
The aims of this study were to develop an understanding of farmers’ perceptions of and risk factors for footrot, including its less severe forms, and other hoof diseases in sheep in New South Wales (NSW). A questionnaire was developed and administered to sheep farmers in Local Land Services (LLS) regions across NSW. LLS staff selected sheep farmers who met the inclusion criteria and farmers completed the questionnaire either by telephone or via the REDCap online survey platform. Descriptive analyses and multivariable logistic regression models were created. The survey was completed by 43 sheep farmers with a median farm size of 1500 Ha and flock size of 2300; footrot was present on 39% of farms while 75.6% had other hoof diseases. A large flock size was identified as the primary risk factor for the presence of footrot whilst the frequency of lameness inspections and an undulating topography were associated with the presence of other hoof diseases. Most farmers agreed that the footrot including its less severe forms can cause production losses and negatively affect animal health and welfare. Flock size, farm topography and animal management practices influenced the presence and impact of footrot and other hoof diseases. As dry environmental conditions limited expression of footrot during the study, further research is required to provide insight into the efficacy of footrot treatments.